2016
DOI: 10.1177/0021998315615653
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical, thermal and surface properties of nanoclay/HDPE nanocomposites produced industrially by melt mixing approach

Abstract: The main aim of this paper is to introduce mechanical, thermal and surface properties of produced industrially HDPE-based nanocomposites. For this purpose, 1.0, 2.0, 3.0, 4.0 and 5.0 wt.% loading of nanoclay-reinforced HDPE nanocomposites made from the HDPE matrix were prepared by the melt mixing method using a compounder system, which consist of industrial banbury mixer, single screw extruder and granule cutting. The effect of nanoclay on mechanical, thermal and surface properties of nanoclay/HDPE nanocomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…The melting peak T m,peak , and onset T m,onset , temperatures and the total heat of fusion obtained from these curves are reported in Table . T m,peak for pristine HDPE was estimated at 132.5 °C, which is a typical value, in the range of 131–134 °C, reported in literature for this polymer . As it can be seen all curves are similar and most of the samples melt at approximately 133 °C.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The melting peak T m,peak , and onset T m,onset , temperatures and the total heat of fusion obtained from these curves are reported in Table . T m,peak for pristine HDPE was estimated at 132.5 °C, which is a typical value, in the range of 131–134 °C, reported in literature for this polymer . As it can be seen all curves are similar and most of the samples melt at approximately 133 °C.…”
Section: Resultssupporting
confidence: 85%
“…The crystallization onset temperature is similar for all materials and near 117.5 °C. Similar values have been reported also in literature . In contrast to HDPE, LDPE usually presents two crystallization peaks, which is an indication of existence of crystallites with various thicknesses, and also an indication of a high degree of branching found in LDPE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have understood from XRD studies that a good dispersion can be achieved by appropriate processing conditions are used in our previous studies. 13,14 In this study, the XRD studies were confirmed with the EDS mapping study performed on the impact fracture surface and, the distribution state was visually revealed. Figure 9 present SEM and EDS mapping images of the impact fracture surface of unfilled HDPE.…”
Section: Resultssupporting
confidence: 59%
“…However, high tensile toughness may not certainly mean high impact toughness. 13,14 Many researchers have reported that the addition of a filler to polymer systems results in a breaking force and impact strength; this behavior has been attributed to weakness in the structure of these two-phase systems caused by stress concentration or discontinuity in stress transfer between dispersed phase and the matrix. The poor interaction between both nanofillers and matrix has bring about the formation of massive filler agglomerates in the polymer matrix, substantially influencing the mechanical response of the industrial product.…”
Section: Resultsmentioning
confidence: 99%